2018
DOI: 10.1088/1755-1315/106/1/012113
|View full text |Cite
|
Sign up to set email alerts
|

Effect of immobilized biosorbents on the heavy metals (Cu2+) biosorption with variations of temperature and initial concentration of waste

Abstract: Abstract. The aims of research is to studying the efficiency of copper removal by combining immobilized microalgae with optimizations of temperature and initial Copper concentration. The research was conducted in batch culture with temperature variations of 25°C, 30°C, and 35°C, as well as initial Cu 2+ concentrations (mg/l) of 3, 5, 10, 15 and 20 using monoculture of S. cerevisiae, Chlorella sp., and mixed culture of them both as immobilized biosorbents. The optimum adsorption of 83.4% obtained in temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…Such a trend is mostly attributed to an increase in the absorptive surface area and the availability of more active binding sites on the surface of the adsorbent. Our results agree with those of Siwi et al (2018) who revealed that the removal efficiency was increased by the increase of initial biosorbent concentration.…”
Section: Discussionsupporting
confidence: 93%
“…Such a trend is mostly attributed to an increase in the absorptive surface area and the availability of more active binding sites on the surface of the adsorbent. Our results agree with those of Siwi et al (2018) who revealed that the removal efficiency was increased by the increase of initial biosorbent concentration.…”
Section: Discussionsupporting
confidence: 93%
“…This technique has been utilised with biomass from Chlorella sp. (Siwi et al, 2018;Wilan et al, 2019;Wilan et al, 2020;Rinanti et al, 2022), Desmodesmus sp. (Widyaningrum et al, 2021), Scenedesmus obliquus (Wilan et al, 2019;Wilan et al, 2020;Rinanti et al, 2022), and Calothrix sp.…”
Section: Microalgae For Heavy Metal Removalmentioning
confidence: 99%
“…There are different immobilization techniques that can be applied for biosorbents, with microbial cells being bonded either on the surface or within a polymer matrix: adsorption, covalent bonding, cross-linking, encapsulation, and entrapment in a matrix (Figure 2) [6,22,[24][25][26]. [23,27].…”
Section: Biosorptionmentioning
confidence: 99%